Association between serum Klotho levels and the prevalence of diabetes among adults in the United States - Wang, Kai; Mao, Yukang; Lu, Miao; Liu, Xianling; Sun, Yan; Li, Zhongming; Li, Yansong; Ding, Yinzhang; Zhang, Jing; Hong, Jian; Xu, Di (Frontiers in Endocrinology, 2022)
Background Diabetes is a critical contributor to the pathogenesis of cardiovascular diseases. Klotho is an anti−aging protein with cardiovascular-renal protective effects. However, the relationship between serum Klotho levels and diabetes remains poorly understood. Objectives This study aimed to investigate the relationship between serum Klotho levels and diabetes in US adults. Methods We analyzed the cross-sectional data obtained from 13751 subjects aged 40-79 years in the National Health and Nutrition Examination Survey (NHANES) (2007–2016). Serum Klotho concentration was measured using an enzyme-linked immunosorbent assay (ELISA) and categorized into four quartiles (Q1-Q4). Multivariate logistic regression and restricted cubic spline (RCS) regression were conducted to explore the association between serum Klotho levels and the prevalence of diabetes. Results As compared with quartile 1, serum Klotho levels in quartiles 2-4 yielded odds ratios (OR) (95% CI) of diabetes of 0.96 (0.80–1.15), 0.98 (0.82–1.18), and 1.25 (1.04–1.50), respectively, after covariate adjustment (P for trend = 0.018). The results implied an increased risk of diabetes. The RCS plot showed a U-shaped relationship linking serum Klotho levels with diabetes (P for nonlinearity = 0.003). Conclusions In summary, a nonlinear and positive association was found between serum Klotho levels and the prevalence of diabetes. Further study is needed to verify the causality of this association and elucidate the underlying mechanisms.